Forgiveness in Adolescents Post-Divorce Parents in the Makassar Bugis Tribe - Muh. Fitrah Ramadhan Umar; Sri Hayati; Titin Florentina (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This study aims to find out the description of forgiveness in post-divorce adolescents in the Bugis-Makassar tribe. The research methodology used is quantitative. The subjects of this study were adolescents aged 12-18 years, ethnic Bugis or Makassar, and whose parents were divorced. There were 179 subjects in this study consisting of 66 men and 113 women. The measurement tool used in this study is the Transgression-Related Interpersonal Motivations Inventory (TRIM-18) to measure forgiveness with a reliability of 0.738. This study uses descriptive analysis techniques with the help of SPSS 25 for Windows software. The results of this study indicate that there are 147 (82.1%) students who have high forgiveness, as many as 31 (17.3%) students who have moderate forgiveness and as many as 1 (0.6%) subject with low forgiveness. This study concludes that the forgiveness of post-divorce adolescents in the Bugis-Makassar tribe is at a high level and most adolescents who have not been able to forgive their parents because they want to take revenge on their parents.